Pengaruh Pembelajaran Di Perguruan Tinggi Dan Pendidikan Keuangan Di Keluarga Terhadap Literasi Keuangan - Lulu Amalia Nusron; Ervina Wahyu Krismiatun; Rani Eka Diansari (Akmenika: Jurnal Akuntansi dan Manajemen, 2021)
This study aims to determine whether there is an effect of learning in higher education and finan-cial education in the family on financial literacy in accounting students of the Faculty of Business, PGRI University Yogyakarta. This research is quantitative and uses primary data, namely ques-tionnaires. This study determined all active stu-dents majoring in Accounting, Faculty of Busi-ness, the University of PGRI Yogyakarta as a population. The sample used as many as 90 re-spondents who fit the criteria that have taken financial management courses. The method used in this study was to distribute questionnaires to respondents using google form and using the SPSS version 25 application to test hypotheses with descriptive statistics, validity tests, reliabil-ity tests, normality tests, and multiple linear re-gression analysis. This study resulted in two var-iables, learning in higher education and financial education in the family, which positively influenced financial literacy in accounting stu-dents at the Yogyakarta Business Faculty. This study's result has implications for lecturers in universities, especially PGRI Yogyakarta Univer-sity, to uphold student's formal financial learn-ing. Also, the results of this study impact the par-ents of students as financial education advisers at home to always maintain what has been taught. For Accounting students, the Business Faculty itself is always able to apply the knowledge of both.Â